High-Fat Programming of Hyperglycemia, Hyperinsulinemia, Insulin Resistance, Hyperleptinemia, and Altered Islet Architecture in 3-Month-Old Wistar Rats. (5th September 2012) - Cerf, Marlon E.; Chapman, Charna S.; Louw, Johan
Abstract : High-fat programming, by exposure to a high-saturated-fat diet in utero and/or during lactation, compromises beta-cell development and function in neonatal and weanling offspring. Therefore, high-fat programming effects were investigated on metabolism and islet architecture in young adult rats. Three-month-old male and female Wistar rat offspring were studied: HFG (maintained on a high-fat diet throughout fetal life), HFP (high-fat diet maintenance from birth to 3 months), and HFGP (high-fat diet maintenance throughout fetal and postnatal life). Control rats were maintained on a standard laboratory diet. Pancreata were double immunolabeled for insulin and glucagon to assess islet morphology and with Ki-67 to determine islet and acinar cell proliferation. HFP and HFGP males were heavier, hyperleptinemic, and hyperinsulinemic. Hyperglycemia presented in HFP males, HFP females, and HFGP males. HFGP males and HFP females were insulin resistant. HFP males displayed beta- and alpha-cell hyperplasia with alpha-cell hypertrophy evident in HFP females. Acinar cell proliferation rates were increased in HFP males. Postnatal high-fat programming induced the most diabetogenic phenotype with high-fat maintenance throughout fetal and postnatal life resulting in a severely obese phenotype. Fetal and postnatal nutrition shapes offspring health outcomes.